Analysis on the impact of router alias resolution - Jian REN; Yu JIANG; Ge GAO (Tongxin xuebao)
Router alias resolution is one of hard problems and important steps for router level Internet topology measurement based on traceroute mechanism,and the topology characteristic of the generated router level topology graph has close relationship with the completeness of alias resolution.The graph with its degrees following power-law distribution was taken as the base-graph,and the shortest paths from one source to others were computed for simulating topology measurement.Experiment results show that it is very probable to see different topology characteristics between the derived graph and the base-graph due to incomplete alias resolution.Most importantly,for large-scale router level topology measurement,the completeness of alias resolution must be improved with the increasing number of probe sources,and in this way the derived topology graph could be approximate to the real topology graph.